Comunicación interna para el fortalecimiento del clima organizacional del Instituto Superior Universitario Bolivariano de Tecnología (ITB), período enero – junio 2022. - Jácome Abril, Adrián (2023)
The purpose of this project is what are the factors involved in the internal communication of the Instituto Superior Universitario Bolivariano de Tecnología (ITB) and analyze its shortcomings to determine an effective solution that improves the work environment that arises within the institution. For this, the use of various research methods and techniques was implemented, for example, the deductive, inductive and analytical method was used to examine the negative aspects found with respect to internal communication between employees and employers. In addition, surveys and interviews aimed at the company's internal staff were used as tools for collecting both qualitative and quantitative data, all with the aim of obtaining relevant information for the research. Thanks to the results obtained, it was determined to carry out an internal communication strategy or plan between the various departments of the educational unit through group activities, talks or workshops with related topics: skills training, dissemination of corporate culture, empowerment of team union, etc., in order to strengthen values and affective ties among the staff working within the establishment. Key words: Communication, work environment, corporate culture.